Eu(rope): (Re)assembling, (Re)casting, and (Re)aligning Lines of De- and Re-territorialisation of Early Childhood. Issue 1 (May 2014) - Jones, Liz; Osgood, Jayne; Urban, Mathias; Holmes, Rachel; MacLure, Maggie
The aim of this paper is to (re)(e)value(ate) current micro- and macropolicies and politics that shape – and are shaped by – conceptualisations of and, in consequence, practices towards young children in a range of institutions/figurations. The 'geopolitical' location for our investigation is Europe, understood as conceptual space(s) as well as (geographical) territory. Whilst we begin by focusing attention on events within an English context, we nevertheless move beyond geographical boundaries. We argue that movements that are currently being undertaken in England are not individual activities. Rather, England is infected and affected by European and global histories, practices, policies, philosophies and epistemologies. We argue that it is the oscillations between different components within a broad European assemblage (human and nonhuman) that makes something happen. Subsequently, we detail and question whether 'happenings' that are occurring in England can be considered as possible creative openings where early childhood education/care could be reassembled 'differently'.